CHANGE AND DEVELOPMENT IN THE ACEHNESE DAYAH SALAFI (A CASE STUDY) - Huwaida, Huwaida (SCAD Independent, 2015)
This is part of research result from a Ph.D thesis which is submitted to Flinders University South Australia. This is a study about the Acehnese dayah salafi and its recent change and development, both in general and in the light of messages from the government about the need for standardisation and regulation of the studies of these Islamic educational institutions. Through a qualitative case study of a purposively selected dayah salafi in Aceh province, Indonesia, this research tried to find how standardising or regulating might affect dayah salafi and their teaching activity. The result is perhaps a kind of snapshot of the current moving situation. To get a variety of views for this research, data were collected, using semi-structured interviews, from various dayah salafi people, from a government departmental officer and from a senior Islamic educational researcher. The research also used other sources of data such as general observation and documents related to this study.